2012
DOI: 10.1007/s10875-012-9747-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Circulatory Levels of Interleukin 17F in Type 1 Reactions of Leprosy

Abstract: The results specify that serum circulatory levels of IL 17F are elevated during T1Rs in the borderline spectrum of the disease and thus may play a role in the regulation of inflammatory responses associated with reactions in leprosy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Given the complex interrelation between inflammatory mediators and immune system cells, studies have suggested the participation of other cellular subtypes such as regulatory T cells, Th3 cells (which have a immunosuppressant profile), and Th17 cells (which have a proinflammatory profile) for better understanding periodontal infections [ 35 , 57 , 73 – 76 ] and the evolution of the infection in leprosy reactional states [ 10 , 62 , 67 , 77 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the complex interrelation between inflammatory mediators and immune system cells, studies have suggested the participation of other cellular subtypes such as regulatory T cells, Th3 cells (which have a immunosuppressant profile), and Th17 cells (which have a proinflammatory profile) for better understanding periodontal infections [ 35 , 57 , 73 – 76 ] and the evolution of the infection in leprosy reactional states [ 10 , 62 , 67 , 77 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena are subdivided into type 1 reactions (T1R) and erythema nodosum leprosum (ENL), which is part of the type 2 reaction (T2R). In the T1R, the type 1 helper (Th1) response predominates in lesions and the serum of patients with high levels of cytokines tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), interleukin-17 (IL-17), and C-X-C motif chemokine 10 (CXCL10) [ 9 ]. Some studies of SARS-CoV-2 infection have reported the presence of a cytokine storm syndrome and a subgroup of patients who progressed to severe forms of the disease, expressing a pro-inflammatory profile in plasma with IL-2, IL-7, TNF-α, and others as significant complications, such as occurs in T1R [ 10 , 11 ].…”
Section: Our Viewmentioning
confidence: 99%
“…During reactions, leprosy patients show increased lympho-proliferation against M. leprae antigens as well as increased expression and release of pro-inflammatory cytokines such as IL-1β, IL-2, IL-12, IFN-γ and TNF-α 2 , 3 . Some cytokines such as IP-10, TNF-α, IL-6, IL-10, IL-12, IL-17F and soluble receptors of IL-2 have also been reported in circulation 4 7 .…”
Section: Introductionmentioning
confidence: 99%